2019
DOI: 10.1371/journal.pgen.1008075
|View full text |Cite
|
Sign up to set email alerts
|

Genomic inversions and GOLGA core duplicons underlie disease instability at the 15q25 locus

Abstract: Human chromosome 15q25 is involved in several disease-associated structural rearrangements, including microdeletions and chromosomal markers with inverted duplications. Using comparative fluorescence in situ hybridization, strand-sequencing, single-molecule, real-time sequencing and Bionano optical mapping analyses, we investigated the organization of the 15q25 region in human and nonhuman primates. We found that two independent inversions occurred in this region after the fission event … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 74 publications
(88 reference statements)
3
17
0
Order By: Relevance
“…We first compared the detected inversions with rearrangements previously reported for macaque (Ventura et al 2007;Antonacci et al 2009;Catacchio et al 2018;Maggiolini et al 2019) and confirmed the orientation of 48 events, which correspond mainly to larger inversions (>130 kbp) (Supplemental Table S2). Conversely, 327 regions (87%), ranging in size from 859 bp to 9 Mbp and amounting to 55.6 Mbp of inverted DNA, were novel and described here for the first time as human/macaque inversions.…”
Section: Comparison Of Human and Macaque Assemblies And Published Literaturesupporting
confidence: 77%
See 1 more Smart Citation
“…We first compared the detected inversions with rearrangements previously reported for macaque (Ventura et al 2007;Antonacci et al 2009;Catacchio et al 2018;Maggiolini et al 2019) and confirmed the orientation of 48 events, which correspond mainly to larger inversions (>130 kbp) (Supplemental Table S2). Conversely, 327 regions (87%), ranging in size from 859 bp to 9 Mbp and amounting to 55.6 Mbp of inverted DNA, were novel and described here for the first time as human/macaque inversions.…”
Section: Comparison Of Human and Macaque Assemblies And Published Literaturesupporting
confidence: 77%
“…To further validate inversions not amenable to FISH, we performed BAC-end sequence (BES) paired mapping of a M. mulatta BAC library (CHORI-250) against the human reference genome. We expect BACs spanning inversion BPs discovered in macaque to be "discordant" when mapped to the human reference genome sequence with their ends mapping farther apart than expected in an incorrect orientation (Ventura et al 2007;Antonacci et al 2009;Catacchio et al 2018;Maggiolini et al 2019). Seventy-six inversions detected as homozygous by Strand-seq had support from macaque discordant BAC clones spanning at least one BP (Supplemental Table S6).…”
Section: Validation Of Inversions In Macaquementioning
confidence: 99%
“…Recurrent inversions on the X chromosome have also been associated with Factor VIII deficiency observed both in humans and dogs, which appears to be mediated by inverted repeats arising independently or homogenized by conversion at the same regions 58 . In a few cases where the underlying mechanism has been investigated 59 62 , individuals carrying inverted haplotypes appear predisposed to higher rates of NAHR either because of SDs evolved in the flanking regions in direction orientation or because SDs become configured to predispose to interchromosomal rearrangement in the heterozygous state 34 , 61 . Related to this, one of the important findings of this study is the ability to distinguish simple inversions from inverted duplications by comparing SD and Strand-seq datasets 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Segmental duplications (SDs) are regions > 1 kbp in length sharing high sequence identity (>90%) and representing roughly 5% of the human genome [1,2]. SDs are enriched in pericentromeric and subtelomeric regions and due to the high sequence similarity between paralogous copies, undergo non-allelic homologous recombination causing structural rearrangements such as duplications, deletions, and inversions [3][4][5][6]. These recombination events are a source of genomic plasticity and variability that can directly increase the number of copies of the genes embedded within SDs [7].…”
Section: Introductionmentioning
confidence: 99%